Swords into Plowshares or Plowshares into Swords?: Isaiah and the Twelve in Intertextual Perspective on Zion - Sweeney, Marvin A. (Toronto journal of theology, 2018)
Scholarly discussion of the synchronic and diachronic formation of the Book of Isaiah and the Book of the Twelve Prophets has begun to recognize the intertextual relationships between these two major prophetic books. Indeed, the Book of the Twelve Prophets appears to be formulated in part as a response to the Book of Isaiah. This paper examines that interrelationship by focusing on the famous swords into plowshares passages in Isaiah 2:2-4; Micah 4:1-5; Joel 4:9-13; and Zechariah 8:20-23 in relation to the expectations of future judgment and restoration in their respective books. Examination of these passages will demonstrate a major debate between Isaiah and the Twelve on the issue of the future of world peace and the political constitution of Israel. The Book of Isaiah envisions a process whereby the ideals of the swords into plowshares passage will be realized when both the nations and Israel suffer judgment on the Day of YHWH. The Book of Isaiah envisions the passing of Davidic kingship as Israel at large is granted the eternal covenant, King Cyrus of Persia is selected as G-d s messiah and Temple builder, and ultimately YHWH is recognized as the true king at the end of the book. The Book of the Twelve envisions a process whereby the ideals of the swords into plowshares passage are realized when a new Davidic king rises to defeat the nations that threaten Israel who then ultimately recognize YHWH by the end of the book.